Abstracts - Dale, Roger; Antikainen, Ari; Normand, Romuald; Vasconcelos, Maria Lúcia; Sousa, Óscar; Duarte, José B.; Silva (and others), Nilce (Revista Lusófona de Educação)
Tradução, para a língua inglesa, dos artigos publicados nesta edição.